miR-16-5p, miR-103-3p, and miR-27b-3p as Early Peripheral Biomarkers of Fetal Growth Restriction - Tagliaferri, Salvatore; Cepparulo, Pasquale; Vinciguerra, Antonio; Campanile, Marta; Esposito, Giuseppina; Maruotti, Giuseppe Maria; Zullo, Fulvio; Annunziato, Lucio; Pignataro, Giuseppe (Frontiers in Pediatrics, 2021)
Current tests available to diagnose fetal hypoxia in-utero lack sensitivity thus failing to identify many fetuses at risk. Emerging evidence suggests that microRNAs derived from the placenta circulate in the maternal blood during pregnancy and may be used as non-invasive biomarkers for pregnancy complications. With the intent to identify putative markers of fetal growth restriction (FGR) and new therapeutic druggable targets, we examined, in maternal blood samples, the expression of a group of microRNAs, known to be regulated by hypoxia. The expression of microRNAs was evaluated in maternal plasma samples collected from (1) women carrying a preterm FGR fetus (FGR group) or (2) women with an appropriately grown fetus matched at the same gestational age (Control group). To discriminate between early- and late-onset FGR, the study population was divided into two subgroups according to the gestational age at delivery. Four microRNAs were identified as possible candidates for the diagnosis of FGR: miR-16-5p, miR-103-3p, miR-107-3p, and miR-27b-3p. All 4 selected miRNAs, measured by RT-PCR, resulted upregulated in FGR blood samples before the 32nd week of gestation. By contrast, miRNA103-3p and miRNA107-3p, analyzed between the 32nd and 37th week of gestation, showed lower expression in the FGR group compared to aged matched controls. Our results showed that measurement of miRNAs in maternal blood may form the basis for a future diagnostic test to determine the degree of fetal hypoxia in FGR, thus allowing the start of appropriate therapeutic interventions to alleviate the burden of this disease.